Inovações Sociais como Meio de Promoção do Consumo Sustentável: Possibilidades e Desafios - Verônica Macário de Oliveira (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
The sustainable consumption proposal as one of the three main objectives of sustainable development focuses on satisfing human needs while at the same time seeking to establish respect for the limits of the ecosystem. Civil society is a protagonist in this process and would mobilize pressures for the necessary institutional changes to occur as well as bottom-up actions such as social innovations that seek to present responses to social problems and to empower localities and leverage resources towards development through of democratic and participatory actions that promote social inclusion, such as fair trade networking practices, food cooperatives, trading and exchange platforms, as well as the creation of local currencies. Thus, this essay aims to discuss how social innovations can contribute to promotion of sustainable consumption, analyzing the possibilities and challenges inherent in this process. Methodologically, a theoretical test was carried out. The results show that social innovation can help to promote sustainable consumption since analyzed from the perspective of the social context, they promote the adoption of new practices, new labor relations, new forms of production and consumption that provoke changes in social relations And renew their relationships in terms of sustainability by increasing the proportion of consumption outside the conventional market often seen as an important contribution to a sustainable local life, despite facing some challenges.